Large gallstone impaction at a Meckel's diverticulum causing perforation and localized peritonitis: report of a case - Maclean, William (Oxford University Press, 2013)
We are reporting a successful laparoscopic resection of a perforated Meckel's Diverticulum (MD) causing localized peritonitis due to an impacted gallstone. MD is a small benign pouch on the wall of the small intestine that is present in ∼2% of the population. It results from a failure of complete obliteration of the omphalomesenteric duct. MD is mainly lined by ileal mucosa; however, other ectopic tissue types can be found including gastric, duodenal, colonic, pancreatic, Brunner's glands, hepatobiliary tissue and endometrial mucosa. Most reported complications include bleeding, infection and obstruction. With relevance to this report, we can find no more than two reports of a large gallstone impacting the neck of the MD and causing ileus, and we were unable to find any reports that mention perforation due to impaction at the neck of an MD.